2021
DOI: 10.1186/s12889-021-11600-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk perception of COVID-19 among sub-Sahara Africans: a web-based comparative survey of local and diaspora residents

Abstract: Background Perceived risk towards the coronavirus pandemic is key to improved compliance with public health measures to reduce the infection rates. This study investigated how Sub-Saharan Africans (SSA) living in their respective countries and those in the diaspora perceive their risk of getting infected by the COVID-19 virus as well as the associated factors. Methods A web-based cross-sectional survey on 1969 participants aged 18 years and above (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
36
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 50 publications
13
36
1
Order By: Relevance
“…The use of an online survey has the potential to result in selection bias and could have unduly excluded residents in SSA without internet access. The preponderance of educated persons in this study is another limitation that is a characteristic of most survey studies in Africa [ 19 , 20 , 37 , 42 ] and elsewhere [ 43 ]. These study findings may not be generalizable to the entire SSA because not all countries in SSA answered the questions.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The use of an online survey has the potential to result in selection bias and could have unduly excluded residents in SSA without internet access. The preponderance of educated persons in this study is another limitation that is a characteristic of most survey studies in Africa [ 19 , 20 , 37 , 42 ] and elsewhere [ 43 ]. These study findings may not be generalizable to the entire SSA because not all countries in SSA answered the questions.…”
Section: Discussionmentioning
confidence: 94%
“…The study has some limitations which should be interpreted within the context of the study. Using a perceived risk score that ranged from 0–8 points may violate some linear regression assumptions [ 19 , 41 ]. The use of an online survey has the potential to result in selection bias and could have unduly excluded residents in SSA without internet access.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of individual characteristics, it is found that demographic factors including gender, age, work, and residence during the pandemic have a significant effect on risk perception. The risk perception scores of people aged 18–28 are lower than those of older respondents who have a job and have a higher level of education have significantly higher risk perception scores than other respondents [ [17] , [18] , [19] ]. Demographic factors are the main determinants of COVID-19 risk perception.…”
Section: Introductionmentioning
confidence: 99%
“…In these countries, vaccine acceptance was positively associated with COVID-19 knowledge and threat regarding COVID-19. However, as information that COVID-19 vaccine-induced death spread within communities [ 38 ], a study indicated a low-risk perception of COVID-19 among Sub-Sahara Africans [ 39 ]. Therefore, fear of adverse effects from vaccines “makes sense”.…”
Section: Discussionmentioning
confidence: 99%